EFFECTIVENESS OF INTERVIEWS IN CRISIS PREVENTION AND DETECTION - Arežina, Vera R.; Lukić, Goran (The Policy of National Security, 2025)
This paper will highlight an interview’s definition, phases, classification and characteristics as a qualitative method. Although planning and preparation are essential phases of an interview, the most crucial phase is interviewing due to various questions, such as introductory, informative, assessments and closing questions. We will stress the importance of assessment questions because by observing the verbal and non-verbal answers of the respondents, it is possible to assess their credibility with a certain degree of accuracy. In an interview with observation, we will indicate verbal and nonverbal signs of a spoken lie, which include a variety of body movements and postures accompanying a verbal response. Well conducting an interview, especially the Peace and Reid model, may prevent and detect various crises such as financial fraud, terrorist attacks, and others.